2011
DOI: 10.5005/jp-journals-10011-1157
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alteration in Serum Lipid Levels in Patients with Chronic Periodontitis Postperiodontal Therapy

Abstract: Aim: There is growing evidence that periodontitis may affect general health. This study was assigned to explore changes in cholesterol levels following nonsurgical periodontal therapy in patients with chronic periodontitis. Materials and methods:Periodontal parameters and lipid profile (total cholesterol, high-density lipoprotein, low-density lipoprotein, triglycerides and very low-density lipoprotein) were evaluated in 50 subjects suffering from moderate to severe generalized chronic periodontitis.Results: At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Another study 36 reported that all lipid parameters decreased after periodontal treatment at the end of 3 months, but only TC and LDL reached statistical significance compared with baseline. One more study 37 reported a reduction of TGL, TC, LDL, and VLDL, with an elevation of HDL. All were statistically significant after periodontal treatment at the end of 3 months.…”
Section: Discussionmentioning
confidence: 98%
“…Another study 36 reported that all lipid parameters decreased after periodontal treatment at the end of 3 months, but only TC and LDL reached statistical significance compared with baseline. One more study 37 reported a reduction of TGL, TC, LDL, and VLDL, with an elevation of HDL. All were statistically significant after periodontal treatment at the end of 3 months.…”
Section: Discussionmentioning
confidence: 98%
“…The studies conducted so far indicate that patients with PD have a higher CV risk compared to individuals with periodontal integrity, and also reveal the presence of pathogenic periodontal agents in the early atheroma plaques. (21) Losche et al, cited by Thombre, demonstrates a relationship between periodontal changes and hyperlipidemia, by linking higher plasma TG levels and lower HDL-cholesterol in patients with periodontal damage, compared to healthy subjects. Thus, is it stood for the role of PD as a risk factor for hyperlipidemia.…”
Section: Lipid Profi Lementioning
confidence: 98%
“…(21,22) Analyzing serum parameters before and after periodontal treatment in a group of 50 patients with PD, Thombre et al showed a positive correlation between periodontal damage and levels of total cholesterol, LDL, VLDL, TG and HDL and a direct correlation between periodontal health and HDL. (21) Cutler et al states that there is a tight correlation between the extent of periodontal damage, plasma lipid concentrations and the presence of anti-Porphyromonas gingivalis antibodies. This is explained by the fact that the high levels of TG may modulate the production of PMN IL-1b, as a consequence of the stimulation induced by P.gingivalis.…”
Section: Lipid Profi Lementioning
confidence: 99%